Evaluation of an interdisciplinary chronic pain program and predictors of readiness for change. Issue 1 (1st January 2019) - Katz, Laura; Patterson, Lisa; Zacharias, Ramesh
ABSTRACT: Background: One in five Canadians experience chronic pain, and interdisciplinary pain programs are well established as the gold standard of treatment. However, not all patients are ready to engage in interdisciplinary treatment for chronic pain. Aims: The aims of this study were to (1) first demonstrate changes in patient-related outcomes after attending a publicly funded 8-week interdisciplinary pain program and (2) evaluate pain-related predictors of readiness for change. Methods: The institution's research ethics board approved this study. One hundred twenty-nine patients completed questionnaires on the first and last day of attending the program. Paired sample t -tests were utilized to evaluate the changes in patient-related outcomes after attending the program, and linear regressions were utilized to evaluate pain-related predictors of the stages of change. Results: Postprogram, there were significant decreases in pain-related interference, fear of pain/re-injury, pain catastrophizing, and symptoms of stress, depression, and anxiety and a significant increase in wellness-focused coping and self-efficacy. Postprogram, patients also demonstrated lower scores in precontemplation and contemplation and higher scores in action and maintenance stages of readiness for change. In predicting precontemplation, fear of pain/re-injury was the sole predictor, and self-efficacy was the sole predictor of the contemplation, action, and maintenance stages. Conclusion: These results demonstrate the short-term benefits of an 8-week interdisciplinary pain program. It is suggested that preprogram interventions targeting kinesophobia for individuals who are precontemplative and self-efficacy for others may be important to facilitate patient engagement.